Nogo receptor complex expression dynamics in the inflammatory foci of central nervous system experimental autoimmune demyelination. Issue 1 (December 2016) - Theotokis, Paschalis; Touloumi, Olga; Lagoudaki, Roza; Nousiopoulou, Evangelia; Kesidou, Evangelia; Siafis, Spyridon; Tselios, Theodoros; Lourbopoulos, Athanasios; Karacostas, Dimitrios; Grigoriadis, Nikolaos; Simeonidou, Constantina
Abstract Background Nogo-A and its putative receptor NgR are considered to be among the inhibitors of axonal regeneration in the CNS. However, few studies so far have addressed the issue of local NgR complex multilateral localization within inflammation in an MS mouse model of autoimmune demyelination. Methods Chronic experimental autoimmune encephalomyelitis (EAE) was induced in C57BL/6 mice. Analyses were performed on acute (days 18–22) and chronic (day 50) time points and compared to controls. The temporal and spatial expression of the Nogo receptor complex (NgR and coreceptors) was studied at the spinal cord using epifluorescent and confocal microscopy or real-time PCR. Data are expressed as cells/mm2, as mean % ± SEM, or as arbitrary units of integrated density. Results Animals developed a moderate to severe EAE without mortality, followed by a progressive, chronic clinical course. NgR complex spatial expression varied during the main time points of EAE. NgR with coreceptors LINGO-1 and TROY was increased in the spinal cord in the acute phase whereas LINGO-1 and p75 signal seemed to be dominant in the chronic phase, respectively. NgR was detected on gray matter NeuN+ neurons of the spinal cord, within the white matter inflammatory foci (14.2 ± 4.3 % NgR+ inflammatory cells), and found to be colocalized with GAP-43+ axonal growth cones while no β-TubIII+, SMI-32+, or APP+ axons were found as NgR+ . Among the NgR+ inflammatory cells, 75.6 ± 9.0 % were microglial/macrophages (lectin+ ), 49.6 ± 14.2 % expressed CD68 (phagocytic ED1+ cells), and no cells were Mac-3+ . Of these macrophages/monocytes, only Arginase-1+ /NgR+ but not iNOS+ /NgR+ were present in lesions both in acute and chronic phases. Conclusions Our data describe in detail the expression of the Nogo receptor complex within the autoimmune inflammatory foci and suggest a possible immune action for NgR apart from the established inhibitory one on axonal growth. Its expression by inflammatory macrophages/monocytes could signify a possible role of these cells on axonal guidance and clearance of the lesioned area during inflammatory demyelination.